65 Immediate Response Of The Supraspinatus Tendon To Loading In Roator Cuff Tendinopathy. (5th September 2014) - McCreesh, Karen; Donnelly, Alan; Lewis, Jeremy
Abstract : Introduction: Loading leads to multiple changes in tendon morphological and mechanical properties, which can be altered in tendinopathy. Reductions in tendon thickness are generally reported after loading in lower limb tendons, with some studies suggesting a reduced response in painful tendons. However, no such studies exist for the rotator cuff (RC) tendons. Therefore, the aim of this research was to examine the short-term effect of loading on thickness of the supraspinatus tendon (SsT) and acromiohumeral distance (AHD) in people with and without RC tendinopathy. Methods participants: Painfree controls (n = 20, 10 Males, Mean age = 43) and people with unilateral RC tendinopathy (n = 22, 12 males, Mean age = 47), were recruited. People with full thickness RC tears, bilateral shoulder pain and those with a history of surgery, were excluded. Both groups provided demographic data, and the shoulder pain group also completed a Numerical Rating Scale (NRS) for average shoulder pain intensity and the Shoulder Pain and Disability Index (SPADI) to assess shoulder disability. Ethical approval was obtained and all participants provided written informed consent. Measurements: Ultrasound images were used to measure acromiohumeral distance (AHD) and SsT thickness. A pilot study indicated excellent inter-rater reliability of these measures (ICC > 0.9), and minimal detectable difference (MDD) values of 0.7 mm for AHD and 0.6 mm for SsT thickness. Measures of AHD and SsT thickness were carried out immediately before, and at 3 intervals after the loading protocol (1 h, 6 h and 24 h). Loading protocol: Following a 5-minute shoulder warm-up, participants were seated on a Biodex 3 isokinetic dynamometer. The painful shoulder was exercised in the RC tendinopathy group, while coin toss determined the exercised side for controls. The exercise protocol involved one bout each of concentric and eccentric shoulder abduction, and external rotation, order randomly determined. Speed was set at 120°/sec, range of motion was from 20º internal rotation to at least 25 external rotation, and from neutral to as close as 90º abduction as was tolerable. Three sets of 10 repetitions of each movement direction were undertaken, ceasing once a fatigue level of 35% of overall torque was reached, or if pain beyond resting level was reported. Results: For the RC tendinopathy group, there was a significant increase in SsT thickness at the one and six-hour time points, however only the six hour difference (0.6 mm, 11%) reached the MDD. There was a small statistically significant reduction (0.2 mm, 4%) in SsT thickness in the control group six hours after exercise, however the mean difference less than the MDD. The AHD reduced significantly in both groups at one hour (exceeding MDD), with recovery to normal by 6 h in controls, and 24 h in the pain group. Discussion: Painful RC tendons showed an altered response to loading and slower return to normal compared to pain-free tendons. The coincidence of reduced subacromial space and thickened SsT in the RC tendinopathy group may provide evidence for an interaction between intrinsic and extrinsic mechanisms of RC tendinopathy.